UPAYA PEMERINTAH INDONESIA DALAM MENINGKATKAN KEAMANAN LAUT WILAYAH PERBATASAN MELALUI KERJASAMA PERTAHANAN INDONESIA-JAPAN MARITIME FORUM - Debora Astuti Sihite; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
As the largest archipelago country in the world, Indonesia has a lot of natural resources that make the cross border crime occurred in the border area. The widespread of cross border crime get the marine-based countries realize the importance of increasing the security in the marine border. By the awareness of the widespread of crosss border crime propels Indonesia to have vision as the global maritime fulcrum. With that visions Indonesia tries to increas the security in the border area by doing cooperation with the maritime-based countries. One of such countries is Japan which also an archipelago countries by establishing Indonesia-Japan Maritime Forum.This research conducted by using neorealism perspective withthe international cooperation theory and maritime security concept, this reseach used qualitative-descriptive method, the data of the research was obtainde by learning related studies, the data used was secunder data derived from memorandum cooperation between Japan and Indonrsia concerning the establishment of maritime forum and other memorandum which established based on the cooperation Indonesia-Japan Maritime. The result of this research shown the actions which done by the Indonesia government in increasing the security of border area by implementing IJMF cooperation is conducting a strategic dialogue consist of the information exchange establishing working group, building the infrastructure in the border area and implementing the cooperation in eradicating cross border crime such as ilegal fishing and drug trafficking. Keywords: international cooperation, cross border crime, Indonesia, Japan, Indonesia attempt, maritime forum